Mechanoionic Transduction of Solid Polymer Electrolytes and Potential Applications. Issue 1 (2016) - Dobashi, Yuta; Allegretto, Graham; Sarwar, Mirza S.; Cretu, Edmond; Madden, John D.W.
ABSTRACT: A novel pressure sensor is proposed exhibiting generative properties from displacement-induced ionic charge separation in gel electrolytes. A mechano-ionic or 'piezo-ionic' effect, in analogy to the well-known piezoelectric effect, is hypothesized to originate from a difference in mobilities between cationic and anionic species causing a localized ionic charge gradient upon application of pressure. This gradient can be detected as a voltage or current by using copper electrodes placed at the sides or at regular intervals along a surface of the gel. The voltage generated may be a result of the local concentration gradient induced by the deformation of the gel or perhaps is the result of some ions moving faster through the porous gel than others. In this work, ionic polymer gels based on Poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) co-polymer were synthesized in situ to incorporate an organic electrolyte consisting of bis(trifluoromethane)sulfonimide lithium salt in propylene carbonate. With two electrodes placed under the gel, the samples were subjected to a sinusoidal mechanical force while open circuit voltage was measured to determine the relationship between electrical signal and mechanical input. The voltages generated are 10's of mV in magnitude at 1 kPa. Results suggest a maximum sensitivity of 25 µV/Pa at 10 mHz, comparable to the voltages expected in piezoelectric polymers such as PVDF (44 µV/Pa for similar dimensions). The non-aqueous, solid-state ionic gels presented in this work provide improved stability and is less prone to evaporation than its aqueous, hydrogel based counterpart. The new mechanism of sensing provides an alternative to the more rigid and less stretchable piezoelectric sensors.